Natural radioactivity, radon emanating power and mass exhalation rate of environmental soil samples from Karabük province, Turkey - Kurnaz, Aslı; Turhan, Şeref; Hançerlioğulları, Aybaba; Gören, Elif; Karataşlı, Muhammet; Altıkulaç, Aydan; Erer, Ahmet M.; Metin, Onur (Walter de Gruyter GmbH, 2019)
Abstract In this study, content of natural radionuclides (226Ra, 232Th and 40K) and radon emanating power and radon mass exhalation rate of surface soil samples collected around industrial province Karabük in which the first iron steel plant was built in 1937 were determined by high-resolution γ-ray spectrometry with a high purity germanium detector. The average activity concentration of 226Ra, 232Th and 40K in soil samples were measured as 30 ± 2, 28 ± 2 and 251 ± 20 Bq kg−1, respectively. The average value of radon emanating power and mass exhalation rate of soil samples were found as 31 % and 19 μBq kg−l s−l, respectively. Assessment of possible radiation hazards to the people due to external exposure was done by estimating the outdoor absorbed gamma dose rate in the air at 1 m above the soil, the corresponding annual effective dose, and the excess lifetime cancer risk. The average outdoor gamma dose rate, annual effective dose, and lifetime cancer risk were estimated as 41 nGy h−1, 51 μSv y−1 and 2.0 × 10−4, respectively. A comparison of the activity and radiological results obtained for the studied samples with the corresponding worldwide average values indicates that the results are below the world average values.
Keywords: Soil; natural radioactivity; excess lifetime cancer risk; radon exhalation rate; outdoor absorbed gamma dose rate; radon emanating power; 13. Climate action; 6. Clean water; 3. Good health